2013
DOI: 10.1155/2013/952698
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Related Late Adverse Events in Hodgkin’s Lymphoma

Abstract: Hodgkin's lymphoma (HL) is one of the most curable hematologic diseases with an overall response rate over 80%. However, despite this therapeutic efficacy, HL survivors show a higher morbidity and mortality than other people of the same age because of long-term therapy-related events. In the last decades, many efforts have been made to reduce these effects through the reduction of chemotherapy dose, the use of less toxic chemotherapeutic agents, and the introduction of new radiation techniques. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…ABVD and BEACOPP may also be associated with side effects not identified in this review. For example, alkylating agents in the BEACOPP regimen can affect fertility [129].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABVD and BEACOPP may also be associated with side effects not identified in this review. For example, alkylating agents in the BEACOPP regimen can affect fertility [129].…”
Section: Discussionmentioning
confidence: 99%
“…The studies identified did not report direct associations of toxicity with RT; however, many treatment-related AEs were reported that have commonly been linked to RT, including nausea, vomiting, infections, skin-related complications, cardiovascular, and pulmonary toxicity. Chemotherapy agents may exacerbate these RT-associated conditions; use of anthracyclines, such as doxorubicin, are associated with an increased risk of heart failure [129,131].…”
Section: Discussionmentioning
confidence: 99%
“…Lower total doses of RT and minimized fields may result in fewer toxicities, which include coronary angiopathy, secondary malignancies, thyroid abnormalities, and pulmonary toxicities. 6 In 2013, Girinsky and colleagues 7 demonstrated that the addition of PET to CT imaging improved delineation of involved node RT with increased clinical target volumes but without increased volume of radiation delivered. Therefore, the addition of PET identified, with higher precision and sensitivity, targetable lymph nodes for RT without necessitating larger radiation volumes.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…6 Patients with a bleomycin containing regimen (all three standard regimens noted earlier) are also at an increased risk of pulmonary toxicity, which can include cough and dyspnea, and lead to potential discontinuation of bleomycin with lingering effects up to a year after discontinuation. 7 The RATHL trial attempted to improve the toxicity profile of ABVD in stages II, III, and IV HL by removing bleomycin from the regimen after two cycles in patients with a negative interim PET/computed tomography (CT) scan. The trial observed a reduction in grades 3 or 4 pulmonary toxicity associated with bleomycin omission but failed to improve on the established progression-free survival rate with ABVD.…”
Section: Introductionmentioning
confidence: 99%